Why do so few patients with heart failure participate in cardiac rehabilitation? A cross-sectional survey from England, Wales and Northern Ireland. Issue 2 (26th March 2012) - Dalal, Hasnain M; Wingham, Jennifer; Palmer, Joanne; Taylor, Rod; Petre, Corinna; Lewin, Robert
Abstract : Objectives: To determine why so few patients with chronic heart failure in England, Wales and Northern Ireland take part in cardiac rehabilitation. Design: Two-stage, postal questionnaire-based national survey. Participants and setting: Stage 1: 277 cardiac rehabilitation centres that provided phase 3 cardiac rehabilitation in England, Wales and Northern Ireland registered on the National Audit of Cardiac Rehabilitation register. Stage 2: 35 centres that indicated in stage 1 that they provide a separate cardiac rehabilitation programme for patients with heart failure. Results: Full data were available for 224/277 (81%) cardiac rehabilitation centres. Only 90/224 (40%) routinely offered phase 3 cardiac rehabilitation to patients with heart failure. Of these 90 centres that offered rehabilitation, 43% did so only when heart failure was secondary to myocardial infarction or revascularisation. Less than half (39%) had a specific rehabilitation programme for heart failure. Of those 134 centres not providing for patients with heart failure, 84% considered a lack of resources and 55% exclusion from commissioning contracts as the reason for not recruiting patients with heart failure. Overall, only 35/224 (16%) centres provided a separate rehabilitation programme for people with heart failure. Conclusions: Patients with heart failure as a primary diagnosis are excluded from most cardiac rehabilitation programmes in England, Wales and Northern Ireland. A lack of resources and direct exclusion from local commissioning agreements are the main barriers for not offering rehabilitation to patients with heart failure.